Telaah: Pengaruh Variasi Jenis Bahan dan Metode Pengawetan Alami Terhadap Kualitas Telur Ayam - Ainun Nafisah; Nurul Annazhifah; Marti Marti; Zahra Nur Fadhilah; Risma Destiana Wiyono; Retno Putri Salsabila Sunardi; Audia Daniati Zahra (Journal of Food and Agricultural Product, 2023)
Chicken eggs are one of the food products that are easily contaminated by microorganisms either directly or indirectly. Contamination generally comes from straw where eggs are laid, soil, air and poultry droppings. Eggs stored at room temperature for more than 10-14 days will undergo chemical and microbiological changes which result in a decrease in quality. One of the things that is needed to address this is to preserve egg products so that the products can be stored for a longer time. The main parameters of egg quality can be observed based on the index of egg yolk and egg white, HU value, and pH value. active ingredients contained in the ingredients, conditions and duration of storage, and methods of preservation. Preservation methods can be done by utilizing natural ingredients that contain active compounds. Active compounds that play a role can be tannins, polyphenols, flavonoids which act as natural antimicrobial substances. Generally, these active compounds will inhibit the entry of microorganisms through the pores of the eggs by forming complex compounds so that the metabolism of microorganisms will be disrupted.Keywords: Active Compounds, Damage, Eggs, Natural Ingredients, Preservation.